Evaluation of School Zoning Policy in Improving Accessibility and Quality of Education in Sidoarjo Regency - Adi Setiawan, M. Wahyu; Mustofa, Amirul (PT. Anagata Sembagi Education, 2024)
This research aims to evaluate the zoning system of education implemented by the Sidoarjo Regency government to accept students who live within the closest radius of the school. The zoning policy aims to provide equal opportunities for every child to receive quality education. This research employs a qualitative method, with data collection through interviews and documentation. The results show that State Junior High School (SJHS) 1 Krian and State Junior High School 2 Wonoayu meet the indicators of effectiveness, adequacy, and accuracy in the zoning policy, but do not meet the indicators of equity and responsiveness. The indicators of accessibility and quality of education indicate that adequacy, responsiveness, and accuracy are appropriate, while effectiveness and equity are still lacking. The education program is still in the adjustment process, which means that access for children with special needs is not yet optimal. Although the zoning policy has successfully improved accessibility and quality of education in both schools, there are still shortcomings due to parents' lack of understanding of this policy. Therefore, more in-depth education is needed to enhance public understanding of the zoning system.